Efektifitas Kebijakan Operasi Ketupat Semeru 2021 dalam Mengendalikan Penularan Covid-19 di Kabupaten Sidoarjo - Fidianing Sopah; Lukman Arif (Mahesa Research Center, 2022)
This article aims to analyze the effectiveness of the 2021 Ketupat Semeru Operational Policy in the of Covid-19. The problem is focused on the results of the policy operation that has been carried out by the Indonesian National Police with the code